Α‐photolabile amine semitelechelic polymers for light‐induced macromolecular conjugation. Issue 4 (24th November 2021) - He, Lirong; Zhao, Hui; Theato, Patrick
Abstract: The use of UV irradiation as a reaction stimulus provides a facile mean to obtain spatial and temporal control over polymer conjugation reactions. In this work, UV irradiation was used to induce an activated ester‐amine conjugation of polymeric building blocks via photo‐induced deprotection of an amine and subsequent reaction with an activated ester, resembling the first example of macromolecular conjugation using light‐triggered activated ester‐amine chemistry. Abstract :